They did it again! Social control responses to repeated incidences of deviance in small groups / ¡Lo han vuelto a hacer! Respuestas de control social a la incidencia repetida de la desviación en grupos pequeños. Issue 3 (2nd September 2018) - Frings, Daniel; Pinto, Isabel R.
Abstract: Deviant group members who break group norms often challenge social validity and group locomotion, invoking varying types of social control responses. The current study ( N  = 95) investigated changes over time in the use of four social control responses of varying severity (persuasion, embarrassment, temporary exclusion and permanent exclusion) employed in response to deviance. It also tested the roles that perceived effectiveness of and social support for various responses play in response selection. Findings show severity of social control response selection is driven by both pragmatic and identity-based concerns: Over time, responses become more severe, driven in part by effectiveness and social support.